Evaluation and Analysis of Next-Generation FY-4A LPW Products over Various Climatic Regions in China - Wenyuan Zhang; Xinyu Xiao; Jinsong Peng; Shubi Zhang; Endrit Shehaj; Gregor Moeller (Atmosphere)
Atmospheric water vapor, a significant constituent of the atmosphere, affects the energy balance between Earth’s atmosphere and space, and its changes play a crucial role in the greenhouse effect. Layer precipitable water (LPW), which represents the column-integral water vapor within a vertical range, is increasingly recognized as a key indicator of atmospheric water vapor distributions and variations. Due to its capability for layer-wise monitoring, LPW products have the potential to offer valuable insights into the characteristics and evolution of climatic regions through refined atmospheric spatiotemporal information. However, the observational quality and spatiotemporal variations of LPW products across different climate zones, e.g., the diverse climatic regions in China, have not been systematically assessed. In this paper, we aim to evaluate and analyze the climatic and seasonal variations of FY-4A LPW products across five climatic regions in China, contributing to a deeper understanding of water vapor variability and providing valuable data for climate change research. A surface pressure calibration algorithm for ERA5 data is developed to calculate accurate ERA5 LPW products. The results show that all four FY-4A LPWs are consistent with ERA5 LPWs, with an overall root mean square error (RMSE) of 2.58, 0.90, 1.30, and 1.01 mm, respectively. Furthermore, FY-4A LPWs are underestimated in the temperate monsoon area and overestimated in the subtropical and tropical monsoon regions, while FY-4A observations agree well with ERA5 reanalysis in temperate continental and plateau mountain zones. These analyses highlight the remarkable climate dependency of FY-4A LPWs and their potential for climate-related studies.